Makna Silaturrahim dalam Al-Qur’an Perspektif Tafsir Tematik - Mohammad Rofiq; Moh. Subhan (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2020)
How important the meaning of friendship in the view of Islam is seen from a number of verses of the Qur'an and Hadith of the Prophet SAW which provide encouragement and benefits for those who connect friendship lines, on the other hand, religion forbids breaking the bonds of friendship with the threat of punishment that is no less severe. Silaturrahim is an urgent matter, even very urgent for us to refresh our memories, academic studies and then take joint action to apply it. Humans as servants of Allah and as social beings should always maintain friendship even though some of our brothers and sisters try to break it. We should keep trying to fix it. Because people who struggle to connect the ties of friendship will get a good reward from Allah SWT for those who break it. Regarding the meaning of friendship in the Qur'an, it will be discussed from the point of view of thematic interpretation.